UNdefined regions: toward a new typology of regions in the UN - De Lombaerde, Philippe; D'Attoma, Marco; Dullaghan, Neil; Umezawa, Hana; Verhelst, Caroline (Frontiers in Political Science, 2023)
Even though the UN interacts with regions and regionalism, a systematic analysis of the development of the regional dimension within their bodies is still needed. Traditional categories identifying simply electoral or operational roles for regions fall short in accounting for their multi-layered and increasing impact. Aiming at formulating a new typology and research agenda in this area, the authors approached the issue inductively. First, they provided a historical mapping of the regional manifestations in the framework of the UN and UN-regional organization interactions. Second, they analysed relevant debates for the UN on peace, security, and sustainability through the lens of the regional dimension. What emerges is that, though vaguely defined and seriously fragmented, regions are largely used as electoral bodies, socio-economic areas, and statistical categories by the UN, that follow historical, cultural, and political rather than purely geographical criteria in their shaping. Besides, in the last 20 years, regions have become crucial for peacekeeping and conflict resolution in specific areas, as well as they are paramount to the implementation of global sustainability goals. All in all, the inductive approach has outlined three dimensions of UN regionalism: regions’ political and operational roles; institutionalized versus non-institutionalized groupings; and their formal versus informal status. Finally, the authors suggest that strengthening partnerships between the UN and regional entities should be a milestone for a new era of networked and multi-layered multilateralism, while the harmonization of statistical regions is desirable at the operational level.